Board of Commissioners Size, Government Ownership, and Anti-Corruption Disclosure: Evidence from Indonesian SOEs (2017-2024) - Putu Sri Jati Ani; Komang Ayu Krisnadewi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2026)
Backgrounds: Corporate transparency relies heavily on anti-corruption disclosure, a critical element for state owned enterprises (SOEs) under constant observation by the government and the public. Yet, empirical studies have produced conflicting findings about the factors influencing this type of disclosure, especially in the context of Indonesian SOEs. Objectives: This research seeks to analyze the impact of two factors, namely the board of commissioners size and government ownership levels, on the disclosure of anti corruption practices within Indonesian SOEs. Methodology: This quantitative study uses secondary data from SOE annual and sustainability reports, selected via purposive sampling. Data analysis was performed using panel data multiple linear regression in STATA. Findings: The findings reveal a positive and significant influence of government ownership on anti corruption disclosure (β = 0.2111; p < 0.001). This result implies that stronger government involvement leads to enhanced transparency and accountability. In contrast, the size of the board of commissioners shows no significant impact on such disclosure (β = −0.0095; p = 0.633). This finding indicates that having more commissioners does not automatically lead to better disclosure practices. Conclusions: This study concludes that government ownership plays an important role in enhancing transparency and accountability, while board of commissioners size is not an effective determinant of anti-corruption disclosure. These findings contribute to the development of agency theory and legitimacy theory by explaining how governance mechanisms and public legitimacy pressures influence corporate transparency practices in SOEs. The findings also provide practical implications for improving corporate governance and transparency in state-owned enterprises.